Pengaruh penggunaan media sosial terhadap atensi selektif dan konsentrasi belajar generasi z - Adzin, Shilham (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has made social media an inseparable part of Generation Z’s daily life, particularly in both social activities and learning processes. The high intensity of social media use often affects individuals’ ability to maintain focus, attention, and learning concentration. This study aims to analyze the influence of social media usage on selective attention and learning concentration among Generation Z. Selective attention refers to an individual’s ability to focus on relevant information while ignoring unnecessary distractions, whereas learning concentration is related to the ability to maintain focus during the learning process. This research employs a quantitative approach with a correlational design. The research subjects are university students categorized as Generation Z, aged between 18 and 24 years old. Data were collected using Likert-scale questionnaires measuring the intensity of social media use, the level of selective attention, and learning concentration. Data analysis was conducted using linear regression tests to determine the relationship between variables. The results indicate that social media usage has a significant influence on selective attention and learning concentration. Excessive use of social media tends to reduce focus ability and increase distractions during learning activities. On the other hand, controlled and educationally oriented use of social media can provide positive impacts on information access and learning motivation. This study is expected to serve as a foundation for developing adaptive learning strategies that align with the characteristics of Generation Z in the digital era.